Approximate solution of linear Volterra integro –differential equation by using Euler polynomial - AMRANE, Khaled; Encadreur: DJAIDJA, Noui (University of M'sila, 2023)
The objective of this dissertation is to find approximate solutions to the second order of Volterra integro-differential equation using the Euler collocation method and the Euler Galerkin method. This memory present various examples to illustrate the accuracy of the proposed methods.
Keywords: Volterra integro-differential equation,Volterra integral equation,Euler polynomial,collocation Method-Galerkin Method.